2015
DOI: 10.1099/mic.0.000035
|View full text |Cite
|
Sign up to set email alerts
|

Novel, host-restricted genotypes of Bordetella bronchiseptica associated with phocine respiratory tract isolates

Abstract: During a succession of phocine morbillivirus outbreaks spanning the past 25 years, Bordetella bronchiseptica was identified as a frequent secondary invader and cause of death. The goal of this study was to evaluate genetic diversity and the molecular basis for host specificity among seal isolates from these outbreaks. MLST and PvuII ribotyping of 54 isolates from Scottish, English or Danish coasts of the Atlantic or North Sea revealed a single, host-restricted genotype. A single, novel genotype, unique from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Seven SNPs were observed in bipA from strain KM22 compared to RB50 and are predicted to result in 4 amino acid replacements: S322G, V813A, E912G, and S1131P. These findings are similar to the results reported in a recent study evaluating virulence gene polymorphisms among B. bronchiseptica seal isolates, in which bipA was found to have the greatest sequence divergence of the genes examined (Register et al, 2015).…”
Section: Comparison Of Bvg-regulated Genes Amongst Sequenced B Broncsupporting
confidence: 86%
“…Seven SNPs were observed in bipA from strain KM22 compared to RB50 and are predicted to result in 4 amino acid replacements: S322G, V813A, E912G, and S1131P. These findings are similar to the results reported in a recent study evaluating virulence gene polymorphisms among B. bronchiseptica seal isolates, in which bipA was found to have the greatest sequence divergence of the genes examined (Register et al, 2015).…”
Section: Comparison Of Bvg-regulated Genes Amongst Sequenced B Broncsupporting
confidence: 86%
“…Phylogenetic analyses were conducted using MEGA6 version 6.05 (Tamura et al 2013). STs for 61 isolates included in this study have been reported previously (Diavatopoulos et al;2005;Rath et al 2008;Register et al 2015a). Those for an additional 21 isolates were deduced from genome sequence data (Register et al 2015b; GenBank accession #NZ_JGWN01000000).…”
Section: Sequence-based Typingmentioning
confidence: 93%
“…Novel patterns were assigned to newly defined RTs. RTs for 78 of the isolates included in this study have been reported previously (Register et al 1997;Register and Magyar 1999;Register et al 2000;Register 2004;Rath et al 2008;Register et al 2015a).…”
Section: Ribotypingmentioning
confidence: 97%
See 2 more Smart Citations